Cultural differences in explicit and implicit support provision and underlying motivations for self-esteem, closeness, and relational concerns - Tanaka, Rina; Zheng, Shaofeng; Ishii, Keiko (Frontiers in Psychology, 2023)
This research explores how culture influences the motivations underlying explicit (emotional and instrumental) and implicit (companionship and attentiveness) support provision. Two studies (N = 1,106) compared the responses of European Americans and Japanese individuals to a close other’s stressful event. The results showed that European Americans were more likely than Japanese to provide explicit support and more motivated to increase the close other’s self-esteem and feeling of closeness. Conversely, Japanese individuals were more likely to provide attentiveness support, motivated by concern for an entire group and a friend. These findings support the motivation as a mediator hypothesis. On the other hand, the culture as a moderator hypothesis applied to the association between concern for an entire group motivation and implicit support provision. Specifically, concern for an entire group motivation predicted companionship support provision only in Japanese, while it predicted attentiveness support provision mainly in European Americans.